PENGARUH KEADILAN ORGANISASIONAL, KEPUASAN KERJA DAN KOMITMEN ORGANISIONAL TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR PADA TENAGA PENGAJAR UNIVERSITAS DIAN NUSWANTORO SAAT PENERAPAN WORK FROM HOME - Raditya Tricahya Rynaldi; Fuad Mas’ud (Faculty of Economics and Business Diponegoro University, 2022)
Covid-19 pandemic that occur in Indonesia forces Higher Education Institution to implement Work From Home (WFH) for every lecturers. This study aims to examine the influence of organizational justice, work satisfaction, and organizational commitment of the lecturers that works for Universitas Dian Nuswantoro Semarang while working from home on their organizational citizenship behavior intention during WFH. The population in this study are lecturers of Universitas Dian Nuswantoro and sample of this study is Assistant Professor of Universitas Dian Nuswantoro. Sample that was used in this study are 106 lecturers of Universitas Dian Nuswantoro. The result of this research shows that organizational justice, work satisfaction, and organizational commitment while working from home have positive and significant influence to OCB intention during WFH